Exploring the effects of migration on smallholder farm households in Kenya and Burkina Faso - Crossland, Mary; Langill, Jennifer Catherine; Elias, Marlène; Vinceti, Barbara; Paez Valencia, Ana Maria (2021)
This brief brings together insights from a cross-country comparative study exploring the effects of rural outmigration on smallholder farm households in Eastern Kenya and the Central Plateau of Burkina Faso. It sheds light on the context-dependent nature of migration and how different types of migration can have different effects on gendered labour relations and household capacities to invest in farming and manage the farm.